Does a gluten-free diet result in nutritional deficiencies? – a review of literature - Świercz, Aleksandra; Żurek, Urszula; Tołwiński, Ignacy; Kędzierska, Zofia; Antkowiak, Klaudia; Dadas, Klaudia; Małachowska, Dominika; Ciecierski-Koźlarek, Hubert; Shved, Kateryna (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Gluten-free diet have gained immense popularity in recent years, both as a treatment for coeliac disease and as a lifestyle choice for those who believe it is healthier. However, concerns have been raised about potential nutrient inadequacies resulting from the elimination of gluten-containing grains. The purpose of this review is to assess the state of knowledge regarding the impact of a gluten-free diet on nutritional status. Materials and methods: A comprehensive search was conducted using electronic database PubMed to identify relevant studies published between 1999 and 2022. Keywords such as "gluten-free diet" and "nutritional deficiencies" were used in combination with Boolean operators to refine the search. A brief description of the state of knowledge: Analysis of studies revealed that individuals adhering to a gluten-free diet may be at risk of nutritional deficiencies including micronutrients such as vitamin D, vitamin E, vitamin B complex along with minerals, in particular iron, zinc, calcium, magnesium as well as fibre. Furthermore, higher levels of fat and sugar were observed in the composition of gluten-free products. Conclusions: Based on the current body of literature, it is evident that a gluten-free diet results in certain nutritional deficiencies. Individuals following gluten-free diet should be aware of potential risks and take appropriate measures to ensure a well-balanced and nutrient-rich diet. Nutritional guidance should be provided to individuals to address specific nutrient deficiencies associated with a gluten-free diet.